Evaluation of Keratinophilic Fungi and Dermatophytes in Garbage Soil around the Beauty Parlours of Betul City (MP): Assessment of fungal contamination in the vicinity of beauty parlours (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Keratinophilic fungi are a highly specialized group of fungi growing on specific substracts containing the complex nitrogenous material keratin. They are potentially pathogenic to man and animals as they include dermatophyte which parasitize man and animals by invading the keratinized layers of epidermis and epidermal appendages.